Mitochondrial CLPP in Health and Disease: Mechanisms, Therapeutic Duality and Emerging Opportunities - Lea Isermann; Aleksandra Trifunovic (Journal of Inherited Metabolic Disease, 2026)
ABSTRACT Mitochondrial CLPP has emerged as an unusual therapeutic target because both increasing and decreasing its proteolytic activity can be beneficial, depending on the cellular and disease context. Pharmacological CLPP hyperactivation drives broad degradation of mitochondrial proteins and can selectively collapse mitochondrial fitness in susceptible tumor cells, an approach now clinically validated by the approval of dordaviprone for mutant diffuse midline glioma. Conversely, reduced CLPP activity can preserve respiratory‐chain components and promote adaptive metabolic and redox remodelling in selected models of mitochondrial disease, neurodegeneration and metabolic dysfunction, with emerging potential in ischaemia‐reperfusion injury. These opposing outcomes reflect the broader role of CLPXP in controlling mitochondrial translation, respiratory‐chain integrity and metabolism rather than acting simply as a general protein quality‐control system. In this review, we discuss the physiological functions and substrate selectivity of CLPXP, the mechanistic basis and clinical development of CLPP inhibitors and activators, and the growing evidence that therapeutic responses depend strongly on tissue identity, metabolic state and the nature of the underlying mitochondrial defect. Together, these findings position CLPP as a context‐dependent therapeutic switch whose activity may need to be tuned in opposite directions to either preserve mitochondrial resilience or selectively dismantle mitochondrial fitness.